The Effectiveness of Educational Support to Orphans and Vulnerable Children in Tanzania and Uganda - Shann, Mary H.; Bryant, Malcolm H.; Brooks, Mohamad I.; Bukuluki, Paul; Muhangi, Denis; Lugalla, Joe; Kwesigabo, Gideon (International Scholarly Research Notices, 2013)
Little evidence is available to assist policy makers and donors in deciding what kinds of programs in developing countries are more likely to be effective in supporting the entry and continuation of OVC in secondary schools. This is particularly important for females whose education has direct bearing on child mortality in the next generation. This study gathered four kinds of educational outcome measures in two East African countries ravaged by the AIDS/HIV pandemic. e goal was to determine whether direct scholarship aid to individual students versus various forms of block grants would be more effective in promoting lower rates ofabsenteeism, lower dropout rates, higher national examination scores, and higher pass rates for OVC of both genders. Insufficient evidence was available for recipients of scholarships, but OVC with block grant support performed as well or better than their non-OVC counterparts, and significantly better than OVC without support. Contrary to popular belief, girls had lower rates of absenteeism. There were no gender differences in dropout. However, boys consistently outperformed girls on academic tests. Insufficient data systems continue to impede more detailed analysis.